PERBAIKAN SISTEM KONTROL PERBAIKAN FAKTOR DAYA PADA POMPA AIR BERBASIS ARDUINO - Alhuda ash Shiddieqy; Sayu Pratiwi; Aan Febriansyah; Surojo Surojo (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
A water pump with a low power factor results in an increase in the value of the current and reactive power, this can result in an increase in the reduction of the water pump efficiency. The purpose of this research is to design a control system to improve the power factor (cos phi) of the water pump automatically using a capacitor bank. When the motor operates, the current, voltage and power factor are read by the PZEM-004T sensor which is then sent to the Arduino. The data from the sensor is used as a basis for calculations to determine the value of the capacitor required by the water pump. Once the capacitor value is known, the Arduino processes the control program to activate the appropriate capacitor bank. This process will take place automatically when the load changes. Based on the test results on one single-phase water pump, the average water pump power factor can be fixed automatically to above 0.9 and the working current of the water pump drops from 0.96 A to 0.73 A as well as the reactive power. There is a difference in the reading from the measuring instrument and the calculation result with an average percentage of 0.2% due to the rounding of the calculation value in the program and also influenced by the accuracy of the reading of the measuring instrument used.